Effect of Thermal Shocking and Quenching on the Degradation Behaviour of a Thin PZT Disc: Thermal Shocking and Quenching Effect on PZT Disc - Pasha, Riffat Asim; Khan, Muhammad Zubair (Biological Sciences - PJSIR, 2010)
Thin lead zirconate titanate discs were subjected to thirty five thermal shocks from two different temperatures in deionized water and their relative dielectric constant, coupling factor and impedance values were measured with a view to investigating the behaviour of thin piezoelectric (PZT) discs at frequency of maximum and minimum impedance. Noticeable differences were observed in the electrical properties of the material, probably due to the change in dipole lengths and their orientations during thermal shocking. The results can be useful in modeling and designing of smart components for predicting their behaviour during such expected shocking conditions prior to fabrication.